2013
DOI: 10.1084/jem.20121588
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid expression associates with enhanced IL-22 production by γδ T cells and innate lymphoid cells and attenuation of intestinal inflammation

Abstract: Retinoic acid attenuates colitis and is associated with increased IL-22 production from γδ T cells and innate lymphoid cells and enhanced antimicrobial peptide expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
243
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 264 publications
(261 citation statements)
references
References 29 publications
9
243
1
2
Order By: Relevance
“…Consistent with the effect of CD4 + T cells, we found that RA inhibits IL-17A production by gd T cells but, interestingly, enhances the production of IL-22 by gd T cells and group 3 ILCs stimulated with IL-1b and IL-23 (80). Furthermore, in vivo administration of RA promotes recovery from intestinal inflammation induced by dextran sulfate sodium or following infection with Citrobacter rodentium, and this is associated with enhanced production of IL-22 and the antimicrobial peptides REG3b and REG3g (80). Consistent with the protective effects of atRA, Chenery et al (81) showed that mice lacking the RA-degrading enzyme CYP26B1 are protected against T cell-induced intestinal inflammation.…”
Section: Impact Of Ra On Gd T Cells Nk Cells and Innate Lymphoid Cellssupporting
confidence: 85%
“…Consistent with the effect of CD4 + T cells, we found that RA inhibits IL-17A production by gd T cells but, interestingly, enhances the production of IL-22 by gd T cells and group 3 ILCs stimulated with IL-1b and IL-23 (80). Furthermore, in vivo administration of RA promotes recovery from intestinal inflammation induced by dextran sulfate sodium or following infection with Citrobacter rodentium, and this is associated with enhanced production of IL-22 and the antimicrobial peptides REG3b and REG3g (80). Consistent with the protective effects of atRA, Chenery et al (81) showed that mice lacking the RA-degrading enzyme CYP26B1 are protected against T cell-induced intestinal inflammation.…”
Section: Impact Of Ra On Gd T Cells Nk Cells and Innate Lymphoid Cellssupporting
confidence: 85%
“…We have shown that the size of these lymphoid organs determined the efficiency by which a viral infection could be cleared at adult age (16). An essential role for vitamin A in adult mice during Citrobacter rodentium infection and dextran sodium sulfate-induced colitis has been shown (14,15), indicating an important role for IL-22 production during intestinal inflammation. However, these studies did not consider the reduced number of SILTs in the absence of dietary intake of vitamin A, which will also have its effect on the efficiency of the immune response.…”
Section: Temporary Postnatal Inhibition Of Ra Signaling Affects Silt mentioning
confidence: 94%
“…For instance, it has been shown that dietary AhR ligands are able to control the function and maintenance of group 3 ILCs postnatally, which consequently has an impact on the formation of CPs and isolated lymphoid follicles (11)(12)(13). Additionally, it was first shown by Mielke et al (14) that not only intestinal gd T cells but also IL-22-producing ILCs are controlled by the active metabolite of vitamin A, retinoic acid (RA). The importance of vitamin A for ILCs was even further established, as in the absence of vitamin A RORg + ILC3s are reduced, whereas group 2 ILCs are enhanced (15).…”
mentioning
confidence: 99%
“…The requirement for Clostridia-induced IL-22 production for the expansion of colonic Foxp3 + Tregs was examined by i.p. injection of 500 μg of clone IL-22JOP (eBioscience), as previously described (39).…”
mentioning
confidence: 99%